CONSUMPTION OF MALANG APPLE (MALUS SYLVESTRIS MILL) AND CALIFORNIA PAPAYA (CARICA PAPAYA L.) JUICE BEFORE EXERCISE ON INCREASING VO2MAX, LUNG VITAL CAPACITY, AND GLUCOSE LEVELS IN AREAS EXPOSED TO AIR POLLUTION - Kusuma Putra, Dea
Background: High-intensity exercise for three weeks could not significantly improve body fitness in areas exposed to air pollution (PM2,5). The purpose of this study was to determine additional nutrients in the form of Malang apple juice and California papaya juice which are balanced with exercise in optimizing the increase in VO2max, lung vital capacity, and glucose levels in areas of high pollution exposure. Methods: This study used a pre-test and post-test control group design. The research location is in Blora, Central Java. The sample is 15 students of class XI from SMK Negeri 1 Blora who are in good health. The sample was divided into three groups, including two experimental groups and one control group. The treatment is divided into two, namely the administration of Malang apple juice and California papaya juice which are given every day for 21 times, while the other treatment is doing fartlek running combined with HIIT with the sample provision of warming up for 5 minutes followed by running for 15 minutes with HRM (90-95%), performed every other day and 9 times (excluding pre-test and post-test). Results: The findings in this study are that the average PM2,5 level in Blora Regency is 51,5 µg/m3 and is included in the not healthy category. The control group did not show significant improvement in increasing VO2max (P=0,26)/(10%), vital lung capacity (P=0,07)/(9%), and controlling glucose levels (P=0.29)/(14%). In the California papaya juice group, there was a significant increase in VO2max (P=0,00)/(22%), lung vital capacity (P=0,004)/(17%), but not significant in controlling glucose levels (P=0,06)/(34%). The Malang apple juice group showed significant improvement in increasing VO2max (P=0,00)/(28%), lung vital capacity (P=0,001)/(29%), and controlling glucose levels (P=0,008)/(48%). Conclusion: Short-term exercise treatment in areas exposed to air pollution is less than optimal in increasing body fitness if it is not balanced with additional nutrition. Malang apple juice showed a better improvement in increasing VO2max (12%), vital lung capacity (26%), and controlling glucose levels (18%) compared to California papaya juice.